Occurement assessment of helminth parasites in Euthynnus affinis from Banten, Indonesia - FORCEP RIO INDARYANTO; MOHAMMAD MUKHLIS KAMAL; NURLISA A. BUTET; RIDWAN AFFANDI; RISA TIURIA (Society for Indonesian Biodiversity, 2024)
Abstract. Indaryanto FR, Kamal MK, Butet NA, Affandi R, Tiuria R. 2024. Occurement assessment of helminth parasites in Euthynnus affinis from Banten, Indonesia. Biodiversitas 25: 4978-4985. As an economically valuable fish, Euthynnus affinis requires regular surveillance and assessment of the prevalence of helminth parasitic infestation in Banten waters, Indonesia. In the districts of Cituis-Tangerang (North Banten), Labuan-Pandeglang (West Banten), and Binuangeun-Lebak (South Banten) in the waters of Banten, E. affinis were collected in November 2023 to January 2024. Seven species of helminth parasitic were identified to infect E. affinis in Banten: Anisakis typica (intensity 1.17; prevalence 14.65%), Tentacularia sp. (intensity 1; prevalence 0.64%), Dinurus sp. (intensity 17.75; prevalence 7.64%), Didymozoid sp. (intensity 2.25; Prevalence 7.64%), Rhadinorhynchus sp. (intensity 24.86; prevalence 87.90%), and Acanthocephalus sp. (intensity 24.86; prevalence 87.90%) are the seven species of helminth parasitic that infect E. affinis in Banten. The overall prevalence of helminth parasitic infection was categorized as moderately prevalence (89.17%) with a moderate intensity (27.32). Despite severe infestations of distinct helminth parasitic species, the mean condition factor (K) values for parasitized and non-parasitized fish did not differ appreciably. Positive allometric growth was observed in both parasitized and non-parasitic fish. Helminth parasitic infection exceeding 80 individuals/fish significantly affects the Gonado Somatic Index (GSI). Fish measuring 25-30 cm in total length were found to be susceptible to helminth parasitic infection; however, there was no correlation between fish length and parasite abundance (r2 = 0.0223). Males had a higher infection rate compared to female fish. There was no statistically significant difference in the abundance of parasites across the three locations. The host's diet was found to affect the parasitic infection. The greatest diversity of parasite species was discovered in Labuan, West Banten.